2020
DOI: 10.5812/semj.98656
|View full text |Cite
|
Sign up to set email alerts
|

A Triple-Blind Randomized Controlled Trial on Impacts of Pioglitazone on Oxidative Stress Markers in Diabetic Kidney Transplant Recipients

Abstract: Background: Oxidative stress as a major mediator of adverse outcomes in kidney transplant recipients who are prone to oxidative stress-mediated injury by pre-transplant and post-transplant conditions. Objectives: The purpose of this study was to assess the effects of Pioglitazone on oxidative stress biomarkers and blood glucose control in diabetic patients receiving insulin after kidney transplantation. Methods: In a triple-blind randomized placebo-controlled trial, sixty-two kidney transplanted diabetic patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A similar study compared pioglitazone and insulin in PTDM; the authors concluded that both agents reduce HbA1c, result in a better lipid profile, and have similar weight gain. None of the two agents showed any interactions with immunosuppressive medications [92]. Many other studies concurred with these findings; Luther and Baldwin [90] found similar findings in a single-arm study using pioglitazone in PTDM.…”
Section: Management Of Ptdm In Outpatient Settingmentioning
confidence: 63%
“…A similar study compared pioglitazone and insulin in PTDM; the authors concluded that both agents reduce HbA1c, result in a better lipid profile, and have similar weight gain. None of the two agents showed any interactions with immunosuppressive medications [92]. Many other studies concurred with these findings; Luther and Baldwin [90] found similar findings in a single-arm study using pioglitazone in PTDM.…”
Section: Management Of Ptdm In Outpatient Settingmentioning
confidence: 63%
“… 102 , 103 Pioglitazone has also been found to reduce oxidative stress through a reduction in the levels of MDA and inhibition of ROS production and inflammatory pathways; this further verifies its potent antioxidant activity. 104 All these findings indicate the role of pioglitazone against stress in the brain via regulation of TRX1, p47phox, and gp91phox activity, and the levels of MDA and ROS.…”
Section: Introductionmentioning
confidence: 86%
“…Most studies are small case series with similar results (Table 2). The largest study-a double-blind randomized controlled trial by Kharazmkia et al comparing pioglitazone plus insulin versus placebo plus insulin-found a decrease in blood in HgbA1C among those kidney transplant recipients on pioglitazone and no effect on cyclosporin levels [66].…”
Section: Thiazolidinedionesmentioning
confidence: 99%